The relationship between alexithymia and theory of mind: A systematic review. (December 2021) - Pisani, Sara; Murphy, Jennifer; Conway, Jane; Millgate, Edward; Catmur, Caroline; Bird, Geoffrey
Highlights: Findings are mixed regarding the link between theory of mind (ToM) and alexithymia. We provide a taxonomy of ToM measures and their relationship with alexithymia. Alexithymia relates to poor ToM where tasks involve emotion recognition. Alexithymia may also relate to a reduced propensity to engage in ToM. This review highlights a need to consider the processes quantified by ToM tasks. Abstract: Theory of Mind (ToM), the ability to represent the mental states of oneself and others, is an essential social skill disrupted across many psychiatric conditions. The transdiagnostic nature of ToM impairment means it is plausible that ToM impairment is related to alexithymia (difficulties identifying and describing one's own emotions), as alexithymia is seen across psychiatric conditions. Whilst many studies have examined links between alexithymia and ToM, results are mixed. Therefore, the purpose of this systematic review is to provide a taxonomy of ToM tests and assess their relationship with alexithymia. Tests are grouped according to whether they assess propensity to engage spontaneously in ToM or accuracy of ToM inferences, with tests further subdivided into those that do, and do not, require emotion recognition. A review of 63 suitable studies suggests that alexithymia is often associated with reduced ToM, and inaccurate ToM when tasks require emotion recognition. This latter finding appears due to impaired emotion recognition, rather than ToM impairment per se . Further directions and considerations for future research are discussed.